Magnesium Preparations in Psychiatry, Addiction Medicine, Neurology and General Medicine (Part I. History) - A. R. Bekker; Yu. V. Bykov; A. O. Shkurat; A. S. Voronina (Acta Biomedica Scientifica)
The use of magnesium preparations in medicine has a long history. According to some sources, first attempts by humans to consume magnesium- and calcium-rich minerals orally, presumably for medicinal purposes, could have occurred even in prehistoric times. First attempts to use natural magnesium-calcium alkaline materials to increase the bioavailability of the alkaloids of some psychoactive plants, such as betel, tobacco, and coca, also date back to prehistoric times.Later, several ancient authors, in particular, Hippocrates II, Claudius Galen and Soran of Ephesus, have described the profound laxative effect of sea salt and of crushed dolomite, as well as a positive effect on the psyche of drinking mineral waters from sources that were found by modern scientists to be rich in magnesium, lithium and bromine. The laxative effect of mineral waters from some sources rich in magnesium, or of salts that were extracted from such sources was known in the Middle Ages. Later, Paracelsus discovered that these salts could be useful not only as a laxative, but also as a sedative.In 1707, Massimiliano Valentini first obtained magnesium oxide, which immediately found its use in medicine, as an antacid, as a mild laxative and skin powder. In 1926, Jacques Leroy was the first to prove the vital importance of magnesium for the physiology of animals.In this article, we thoroughly review the history of the medicinal use of magnesium preparations and the history of studies of biological role of magnesium, from antiquity to modern times.